2017
DOI: 10.3390/ijtpp2030012
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Combustor Swirl on Pressure Losses and the Propagation of Coolant Flows at the Large Scale Turbine Rig (LSTR): Experimental and Numerical Investigation

Abstract: The aerothermal interaction of the combustor exit flow on the first vane row has been examined at the Large Scale Turbine Rig (LSTR) at Technische Universität Darmstadt (Darmstadt, Germany). A baseline configuration of axial inflow and a variation of swirling combustor inflow have been studied. The nozzle guide vane (NGV) featured endwall cooling, airfoil film cooling and a trailing edge slot ejection as well as NGV-rotor wheel space purge flow. CO 2 is injected for coolant flow tracing. The results are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…However, previous experimental campaigns in a wind tunnel have shown that the wake is completely reabsorbed at stator leading edge [20]. As such, the aforementioned flow features of the generated swirl make the generated vortex comparable to what documented in literature [16,17,25,26].…”
Section: Generated Disturbancesupporting
confidence: 72%
“…However, previous experimental campaigns in a wind tunnel have shown that the wake is completely reabsorbed at stator leading edge [20]. As such, the aforementioned flow features of the generated swirl make the generated vortex comparable to what documented in literature [16,17,25,26].…”
Section: Generated Disturbancesupporting
confidence: 72%
“…In Ref. [23], additional loss cores were observed with swirl; these were attributed to interaction between the swirl vortex and the HP vane (rather than interaction between the swirl vortex and the cooling flows). Similar interactions were reported in the linear cascade study reported by Jacobi et al [24].…”
Section: Introductionmentioning
confidence: 98%
“…Experiments have been conducted using a 1.5-stage research turbine with film-cooled HP vanes and endwalls. These studies have focused on the robustness of the endwall cooling system to swirl [22] and on the total pressure losses and vane and endwall coolant migration with swirl [23]. Both studies reported significant reductions in endwall cooling effectiveness with swirl: coolant was redistributed, leaving some surfaces virtually uncooled.…”
Section: Introductionmentioning
confidence: 99%
“…The large scale turbine rig at the Technical University Darmstadt, described by Krichbaum et al [18], has been used for several detailed studies of combustor-turbine interactions effect on time-averaged quantities. Werchnik et al [19,20,21] traced cooling flows and measured Nusselt number and cooling effectiveness with different amounts of film cooling with axial and swirling inflow.…”
Section: Introductionmentioning
confidence: 99%